A Semiotics Analysis On The Use Of Emoticons In Inter-Personal Communication On Facebook Social Media - Sompotan, A G Y (Journal of Educational Method and Technology, 2019)
Facebook social media is one of the most popular social media in various circles, ranging from teenagers to adults using this application. Facebook is one place to share expressions or information that is in great demand. One of the facilities available on Facebook is emoticons. Currently Facebook users use emoticons to express their feelings as a sign of response to an upload made by someone else as a message sender. There are various kinds of emoticons in the Facebook application such as love, smile, lauge, flower and many more. Each emoticon is a sign that has an object and raises an interpretant in the minds of users of this application. The method used in this study is descriptive qualitative with the technique of collecting data on observation, interviews, documentation studies and literature studies. The results of this study are descriptive data analysis of the meaning contained in the use of emoticons is to reinforce the contents of the message, provide support, insinuate someone, express feelings of sadness or feelings of joy, feeling embarrassed, giving encouragement or encouragement, apologizing and expressing gratitude. The use of emoticons must be appropriate so there is no mistaken interpretation of the recipient of the message.Â Keywords: Emoticons; Meanings; Semiotics; Social Media; Facebook.